Renoprotective Effect of Pitavastatin against TAA-Induced Renal Injury: Involvement of the miR-93/PTEN/AKT/mTOR Pathway - Marawan A. Elbaset; Bassim M. S. A. Mohamed; Passant E. Moustafa; Tuba Esatbeyoglu; Sherif M. Afifi; Alyaa F. Hessin; Sahar S. Abdelrahman; Hany M. Fayed (Advances in Pharmacological and Pharmaceutical Sciences)
This research investigated if pitavastatin (Pita) might protect rats’ kidneys against thioacetamide (TAA). By altering the PTEN/AKT/mTOR pathway, pitavastatin may boost kidney antioxidant capacity and minimize oxidative damage. Statins have several benefits, including antioxidant and anti-inflammatory characteristics. The principal hypothesis of this study was that Pita can regulate the miR-93/PTEN/AKT/mTOR pathways, which is thought to be responsible for its renoprotective effects. The experiment divided male rats into four groups. Group 1 included untreated rats as the control. Group 2 included rats which received TAA (100 mg/kg intraperitoneally thrice a week for two weeks) to destroy their kidneys. Groups 3 and 4 included rats which received Pita orally at 0.4 and 0.8 mg/kg for 14 days after TAA injections. Renal injury increased BUN, creatinine, and MDA levels and decreased glutathione (GSH) levels. Pitavastatin prevented these alterations. TAA decreased PTEN and increased miR-93, Akt, p-Akt, mTOR, and Stat3 in the kidneys. Pitavastatin also regulated the associated culprit pathway, miR-93/PTEN/Akt/mTOR. In addition, TAA induced adverse effects on the kidney tissue, which were significantly ameliorated by pitavastatin treatment. The findings suggest that pitavastatin can attenuate renal injury, likely by regulating the miR-93/PTEN/Akt/mTOR pathway. This modulation of the pathway appears to contribute to the protective effects of pitavastatin against TAA-induced renal injury, adding to the growing evidence of the pleiotropic benefits of statins in renal health.